1978
DOI: 10.3109/00952997809029257
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Illicit Drug Use: Follow-up Study of Treatment Admissions to DARP during 1969-1971

Abstract: The present study was based on follow-up data on 1409 persons interviewed 4 to 6 years after admission to drug treatment in the Drug Abuse Reporting Program (DARP). The admissions to DARP occurred in 1969-1971, and for most persons the follow-up data included 3 or more years after termination of DARP treatment. The study focused on variations in alcohol consumption associated with post-DARP drug use and treatment status. The results indicated that use of alcohol and non-opioid drugs (particularly marijuana) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…It is possible that more in-depth qualitative studies will also shed light on this interrelationship; however, it is likely that there are considerable individual differences at play, suggesting that subgroups of recovering users might be especially at risk (e.g. [16]). For example, Lehman & Simpson [20] argued that substitution with alcohol might be higher in individuals with a history of alcohol abuse and familial alcoholism.…”
Section: Does Alcohol Become a Substitute Addiction In Those Recoverimentioning
confidence: 94%
See 4 more Smart Citations
“…It is possible that more in-depth qualitative studies will also shed light on this interrelationship; however, it is likely that there are considerable individual differences at play, suggesting that subgroups of recovering users might be especially at risk (e.g. [16]). For example, Lehman & Simpson [20] argued that substitution with alcohol might be higher in individuals with a history of alcohol abuse and familial alcoholism.…”
Section: Does Alcohol Become a Substitute Addiction In Those Recoverimentioning
confidence: 94%
“…The DARP studies [15,16] indicate that overall alcohol use increased post-treatment at the 1-and 6-year follow-up time-points while drug use decreased, suggesting indirectly that substitution may be occurring. Simpson and colleagues [16] found that a small group of participants reported a direct inverse relationship between quitting heroin use and increasing alcohol use post-treatment (13%).…”
Section: Does Alcohol Become a Substitute Addiction In Those Recoverimentioning
confidence: 98%
See 3 more Smart Citations